Religious Bodies as Catalyst For National Development in Africa: The Case of The Living Faith Church - Omodunbi, Olumide Olumuyiwa; Akinrinde, Olawale Olufemi; Ige, Richard; Olawole, Oluwadamilare (Universitas Negeri Semarang, 2021)
Politics and religion overtime have become two sides of a coin. This is particularly through of Africa, Nigeria inclusive, due to the nature of colonialism that accompanied introduction of Christian religion. No matter how conceived, the activities of the various missionary bodies that came with colonialism brought about development to Nigeria in all spheres of live especially in the education sector. This can be attested to by many schools set up by the Christian missionaries that provided quality education for many generations during and after colonial rule in the country. This paper attempts to investigate the activities of the Living Faith church (Winners Chapel) in bringing development through education. The paper found that the Living Faith church have invested vigorously in the education sector as manifested in the establishment of two Universities and chains of Secondary and Primary schools across the country that have continued to train scores of Nigerians and in turn contributing to the development of the country. Although it has been argued that the type of education provided by this church is too expensive and targeted at the elites when compared to the education provided by the early Christian missionaries. The paper concludes that since governmental authorities at various levels have continued to neglect the education sector in spite of the teeming yearning of Nigerians for quality education, the cost of ignorance cannot be compared to the services rendered by the Living faith church in the education sector and thereby contributing its own quota to the development of Nigeria. Keywords: Religion, Church, Development, Winners Chapel, Education